2015
DOI: 10.1186/s13024-015-0014-y
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-responsive transactivator (CREST) protein shares a set of structural and functional traits with other proteins associated with amyotrophic lateral sclerosis

Abstract: BackgroundMutations in calcium-responsive transactivator (CREST) encoding gene have been recently linked to ALS. Similar to several proteins implicated in ALS, CREST contains a prion-like domain and was reported to be a component of paraspeckles.ResultsWe demonstrate that CREST is prone to aggregation and co-aggregates with FUS but not with other two ALS-linked proteins, TDP-43 and TAF15, in cultured cells. Aggregation of CREST affects paraspeckle integrity, probably by trapping other paraspeckle proteins with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 58 publications
2
48
2
Order By: Relevance
“…Primary cultures of mouse hippocampal neurons were prepared from P1 litters of WT and Neat1 -/mice as described previously (Kukharsky et al, 2015). Neurons were transfected with pEGFP-C1 plasmid using Lipofectamine2000 (Life Technologies) and imaged 24 h post-transfection, using BX61 microscope equipped with F-View II camera and CellF software.…”
Section: Primary Mouse Hippocampal Culturesmentioning
confidence: 99%
“…Primary cultures of mouse hippocampal neurons were prepared from P1 litters of WT and Neat1 -/mice as described previously (Kukharsky et al, 2015). Neurons were transfected with pEGFP-C1 plasmid using Lipofectamine2000 (Life Technologies) and imaged 24 h post-transfection, using BX61 microscope equipped with F-View II camera and CellF software.…”
Section: Primary Mouse Hippocampal Culturesmentioning
confidence: 99%
“…SS18L1 encodes the calcium-responsive transactivator (CREST) protein which is an essential component of the nBAF neuron-specific chromatin remodeling complex that is related to the yeast SWI/SNF chromatin remodeling complex [49][50][51]. Overexpression of CREST inhibits neurite outgrowth in cultured neurons and causes retina degeneration in transgenic Drosophila [48,52]. Also, CREST co-immunoprecipitates with FUS in neuron lysates [48,52].…”
Section: Introductionmentioning
confidence: 99%
“…In cultured cells, transformed CREST forms predominantly nuclear dots with some cytoplasmic foci. Also, like other ALS associated proteins, CREST is recruited to stressinduced ribonucleoprotein particle (RNP) granules [52,53]. RNP proteins must reversibly aggregate in physiological granules as part of their normal cellular function, but this ability to aggregate could lead to the formation of pathological aggregates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other less common gene mutations have also been reported in the last decade. These include mutations in ubiquilin-2 gene (UBQLN2), optineurin (OPTN), angiogenin (ANG), heterogeneous nuclear ribonucleoprotein A1 (hnRNPA1) and calciumresponsive transactivator (CREST) [64][65][66][67] . Some researchers have found that there is correlation between the site of onset and gene mutation.…”
Section: Genetic and Pathological Overlaps Between Als And Ftdmentioning
confidence: 99%